Understanding Bahrain’s labour immigration policy-making process during labour markets reforms process 2002-2016: interest groups intermediation and policy networks - Alabbas, NOOR (2020)
This thesis stems from interest in understanding the labour immigration policy-making in Bahrain by examining the role of different actors and considering how their involvement can produce changes to policy outcomes. The thesis examines the labour immigration policy-making process between 2002 and 2016. During this time, the Economic Development Board (EDB) initiated the labour market reform process (LMRP). The Labour market reform process introduced new policies to manage the immigrant labour in Bahrain after granting them work visas. Thus, this thesis will cover the discussion and negotiations in relation to the LMRP. This will include covering the formation of LMRP, the negotiation over the draft law on the regulation of the labour market annexed to the Royal Decree No. (25) for 2005, the negotiation over implementing labour market policies, and the adjustment of the reform outcomes after the Bahraini uprising in 2011. The findings are based on data collected from 23 personal interviews with actors from different government, semi government organisations, and different interest groups. The research used several documents such as parliamentary and Shura minutes, media articles, and documents received from participants during field work. The thesis builds its understanding of the role of different actors in affecting policy outcomes through the perspective of policy network analysis. The policy network is a framework for repeated interactions between different actors where the role of actors and context in affecting policy outcomes can be examined. The actors within the network may interact due to shared beliefs interests, or a need to access each other’s resources. The policy network analysis approach has proved to be useful in highlining the role of different actors during the process. The conclusion of this thesis provides a new narrative regarding the role of different actors. The literature that discusses the LMRP and the role of different actors focuses on analysing the position and effects of different actors as shaped by the division of power within the ruling family. However, with the use of the policy network analysis, the thesis concludes that the capacity of actors to influence policy outcomes is not solely dependent on the internal power struggle within the ruling family. The need for businessmen to finance the labour market reform project was a source of influence over the policy outcome in 2005. The deal they made with the EDB continued to be influential after 2011. In, addition, the businessmen were able to influence job’s localisations policies through its dialogue with Labour market regulatory authority as the two parties shared beliefs in less rigid localisation policies. The Parliament had its role in affecting the outcome through negotiation with the EDB over the inclusion of domestic labour as a tool to reform of the labour market. The MPs were influential in this matter as part of a trade-off process between the inclusion of domestic labour and other related issues of reforms.